Analysis of Fiscal Rules in the European Monetary Union - Damir Šehović (Journal of Central Banking Theory and Practice, 2015)
The EMU fiscal system is specific in many areas compared to other classic fiscal systems of national states. Specific features mainly reflect in the implementation of economic policy within the EMU which is carried out by combining a common centralized monetary policy under the ECB jurisdiction and decentralized fiscal policies under the jurisdiction of the member states. The member states' sovereignty in governing their fiscal policies is one of the key causes of the EU fiscal system underdevelopment, i.e. its indigent structure in relation to "standard fiscal systems". More indigent structure of the EU fiscal system is reflected in the fact that it consists of only three segments. The first one refers to the EU budget which is also the only instrument for implementing fiscal policy at the supranational level. The second one refers to the harmonization of taxation systems in accordance with inputs and other legislation adopted at the EU level with the aim of fostering the single internal market. Finally, the third segment refers to the fiscal policy coordination of the EMU member states related to appropriate fiscal rules, which mainly stem from the Maastricht convergence criteria and the Stability and Growth Pact.
Keywords: E52; E61; E62; 330; fiscal policy; EMU; fiscal rules; Stability and Growth Pact; reform